2019
DOI: 10.2196/12881
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Spatiotemporal Factors Associated With Sentiment on Twitter: Synthesis and Suggestions for Improving the Identification of Localized Deviations

Abstract: Background Studies examining how sentiment on social media varies depending on timing and location appear to produce inconsistent results, making it hard to design systems that use sentiment to detect localized events for public health applications. Objective The aim of this study was to measure how common timing and location confounders explain variation in sentiment on Twitter. Methods Using a dataset of 16.54 million English-language tweet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Parabhoi (2019) analysed the sentiments of tweets from Twitter of ten university libraries ranked in World University ranking 2019 using Mozdeh and reported that the Bodleian Library of Oxford University library is high on positive sentiments and exhibition and archive are revealed to have top word frequency. Shah et al. (2019) used a dictionary-based sentiment analysis technique to detect the variation of Twitter posts among 100 cities with the time frame of July 13th to November 30th, 2017 identifying the positive sentiments and negative sentiments by comparing the time, location and social interactions on Twitter.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parabhoi (2019) analysed the sentiments of tweets from Twitter of ten university libraries ranked in World University ranking 2019 using Mozdeh and reported that the Bodleian Library of Oxford University library is high on positive sentiments and exhibition and archive are revealed to have top word frequency. Shah et al. (2019) used a dictionary-based sentiment analysis technique to detect the variation of Twitter posts among 100 cities with the time frame of July 13th to November 30th, 2017 identifying the positive sentiments and negative sentiments by comparing the time, location and social interactions on Twitter.…”
Section: Literature Reviewmentioning
confidence: 99%
“…( 2011 ) and sentiment analysis Shah et al. ( 2019 ). However, recent studies have shown that such models may have biasness and discrimination against different races and genders.…”
Section: General Stdm Challenges and Research Gapsmentioning
confidence: 99%
“…The spatiotemporal analysis of social data is an evolving area. It has different tasks such as density estimation [295], collaborative filtering for recommender systems [205,152] and sentiment analysis [241]. However, recent studies have shown that such models may have biasness and discrimination against different races and genders.…”
Section: Socialmentioning
confidence: 99%